KS01.3.A Tumoral MHC class II expression in gliomas drives T cell exhaustion. (9th September 2021) - Chih, Y; Sahm, K; Sadik, A; Bunse, T; Trautwein, N; Pusch, S; Stevanovic, S; Opitz, C; Deimling, A; Wick, W; Sahm, F; Bunse, L; et al.
Abstract: BACKGROUND: Neoepitopes are presented on major histocompatibility class II (MHCII) molecules. In glioma, for instance, the recurrent driver mutation IDH1R132H was shown to bear an MHCII-restricted epitope in preclinical and clinical vaccine studies. The general relevance of MHCII expression in glioma for antitumor immunity, however, remains unknown. Here we evaluate stromal and tumoral MHCII expression, functionality, and its association with survival in gliomas. MATERIAL AND METHODS: Immunostaining of human glioma tissues was used to identify tumoral, endothelial, and microglial MHCII expression and to enumerate T cell infiltrates. To gain insights into tumoral MHCII expression, bulk transcriptomic data from TCGA and single-cell transcriptomic data from publicly available datasets were analyzed. MHC ligandome analyses of an MHCII + glioma cell line and human glioma tissues were used to determine the functionality of MHCII in vitro and ex vivo . Functional in vitro co-culture assays with an HLA-DR-matched tetanus toxoid (TT) epitope-overexpressing glioma cell line and in vitro -expanded TT-reactive T cells from healthy donors were used to examine direct target recognition by T helper cells. CRISPR-Cas9-mediated knockout of MHCII in preclinical hypermutant glioblastoma cell line GL261 was employed to further validate the consequences of tumoral MHCII expression and to probe potential clinical intervention with existing therapies. RESULTS: MHCII is expressed in the majority of gliomas and associated with increased infiltration of T cells. In 10% of the analyzed glioma tissues and a subset of single cells, tumoral MHCII expression is detected. Clinical and transcriptomic data reveal that tumoral MHCII is associated with poor prognosis, cytokine responses, immune inhibition and T cell differentiation. Ligandome analyses evidence presentation of peptides by MHCII molecules on glioma cells. In in vitro assays, TT-reactive T helper cells specifically produce IFNg when co-cultured with MHCII + glioma cells upon the presence of co-stimulation. In agreement with the clinical data, preclinical murine models demonstrate that tumoral MHCII expression leads to reduced survival. Co-culture assay shows that tumoral MHCII results in upregulation of PD-1 on T helper cells antigen-specifically. Concordantly, immune checkpoint blockade (ICB) therapy slows the disease progression of mice carrying MHCII + tumors. CONCLUSION: MHCII is expressed in gliomas by a subset of tumor cells. Although tumoral MHCII is functional, it is associated with poor survival in both clinical data and preclinical models. T cell exhaustion induced by tumoral MHCII expression can, in part, be overcome by ICB in vivo . Further experiments are required to decipher tumor cell intrinsic and microenvironmental consequences of tumoral MHCII expression.